2013
DOI: 10.1155/2013/393787
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity, Ovicidal Action, and Median Lethal Concentrations (LC50) of Entomopathogenic Fungi against Exotic Spiralling Whitefly,Aleurodicus dispersusRussell

Abstract: Biological control using entomopathogenic fungi could be a promising alternative to chemical control. Entomopathogenic fungi, Beauveria bassiana (Balsamo) Vuillemin, Metarhizium anisopliae (Metschnikoff) Sorokin, Lecanicillium lecanii (Zimmerm.) Zare and Gams, and Paecilomyces fumosoroseus (Wize) Brown and Smith, were tested for their pathogenicity, ovicidal effect, and median lethal concentrations (LC50) against exotic spiralling whitefly, Aleurodicus dispersus Russell. The applications were made at the rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…Earlier, Eyal et al (1992) Data analyzed with least squares means and means separated using LSD (P < 0.01; Henderson and Tilton, 1955 after application. Earlier, Boopathi et al (2013) reported that L. lecanii had more pathogenicity against A. dispersus under laboratory conditions. Amounts of I. fumosorosea hyphal growth and sporuletion were visibly greater, and faster than the other entomopathogenic fungi.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Earlier, Eyal et al (1992) Data analyzed with least squares means and means separated using LSD (P < 0.01; Henderson and Tilton, 1955 after application. Earlier, Boopathi et al (2013) reported that L. lecanii had more pathogenicity against A. dispersus under laboratory conditions. Amounts of I. fumosorosea hyphal growth and sporuletion were visibly greater, and faster than the other entomopathogenic fungi.…”
Section: Resultsmentioning
confidence: 93%
“…Wraight et al (1998Wraight et al ( , 2000 observed equal pathogenicity of I. fumosorosea against nymphs of B. argentifolii under laboratory conditions. Studies by Boopathi et al (2013) reported that I. fumosorosea had more pathogenicity against A. dispersus under laboratory conditions.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…This work may be considered as the first record of the high pathogenicity of species of Fusarium, Epicoccum, Scopulariopsis and Aspergillus niger against C. capitata. Fusarium species were considered as saprophytic fungi [35] and also reported to be pathogenic to Aphis gossypii Glover [30], Scirtothrips dorsalis Hood [40,41], Polyphagotarsonemus latus Banks [40], Aleurodicus dispersus Russel [42] and to other pests [37]. Species of Aspergillus have been found associated with a large number of insects such as larvae of bees (A. niger), Troglophilus neglectus (A. niger, A. ochraceus), and Culex pipiens (A. ochraceus) [38,39,43].…”
Section: Entomopathogenic Fungi Isolatedmentioning
confidence: 99%